Agrobiodiversity as a Reservoir of Medicinal Resources: Ethnobotanical Insights from Aymara Communities in the Bolivian Andean Altiplano - Simón Cocarico; Diego Rivera; Stephan Beck; Concepción Obón (Horticulturae)
This study investigates the medicinal potential of cultivated plants and weeds in Aymara communities around Lake Titicaca. It highlights the intricate connection between horticultural diversity and traditional healing practices. Through ethnobotanical research involving 228 informants across multiple locations in Bolivia, we documented 239 medicinal plant species, focusing on the diversity within cultivated landscapes. Among these, 56 species are cultivated crops, 17 are agricultural weeds, and 19 species have dual status, serving as both wild and cultivated plants depending on environmental conditions. Women are repositories of knowledge for 81% (193) of total medicinal plant species, while men know 47% (113) of species. Women display dominant knowledge of cultivated species (89%, or 50 species) and purchase medicinal plants from local markets; women know 92% (24 species) vs. men’s 15% (4 species). Our results suggest men may use a smaller set of species more frequently, while women know and use a broader range of species. The analysis of plant life forms revealed the significant medicinal roles of perennials, annuals, subshrubs, and shrubs, which together account for over 67% of the documented species and 73% of the use reports. Arboreal species are present but have a comparatively smaller role in traditional medicine. In total, we recorded 1477 use reports addressing 260 pathologies across 28 major health categories. Notably, cultivated plants and weeds represent 38.8% of the medicinal species, highlighting their essential role in local healthcare practices. By assessing the contributions of native and introduced species, this study sheds light on the complex botanical resources integrated into Aymara agricultural systems. These findings deepen our understanding of medicinal plant diversity and underscore the importance of agrobiodiversity as a cornerstone of community health and cultural resilience in the Andean region. This research also emphasizes the often-overlooked medicinal value of cultivated landscapes and agricultural margins.